Scope of Data Journalism for Investigation Reporters in Pakistan - Dr. Taha Shabbir; Imran Arif; Saeed Memon; Mohsin Wazir; Zafar Siddiqui (Research Parks Publishers, 2021)
Data Journalist can be defined as Journalists who work with numbers